Bevacizumab plus chemotherapy versus chemotherapy alone for preventing brain metastasis derived from advanced lung cancer. (3rd May 2016) - Fu, Yan; Hu, Jia; Du, Nan; Jiao, Shunchang; Li, Fang; Li, Xiaosong; Ma, Junxun; Zhao, Hui; Kang, Huanrong
Abstract : This retrospective analysis evaluated the mechanism of bevacizumab plus chemotherapy (BV+CT) for preventing brain metastasis derived from lung cancer. From the total of 159 patients with advanced non-small cell lung cancer (NSCLC), 110 received BV+CT and 49 received CT. After medication, both groups had 15 patients with brain metastases (14 vs 31%, P  < 0.05). With BV+CT treatment, 40 patients (33.89%) survived, whereas only 11 patients (18.64%) survived with CT treatment. The outcome for the BV+CT group was significantly better than that for the CT group only for vascular endothelial growth factor (VEGF)-positive patients. A post-treatment with BV+CT was significantly reduced than with CT only for patients with high carbonic anhydrase-9 (CA9) expression. This retrospective analysis provides supportive evidence that BV+CT can significantly reduce the incidence of brain metastasis in patients with advanced NSCLC compared with CT alone. Vascular endothelial growth factor -positive patients may benefit more from BV treatment and the outcomes with BV may be related to CA9 expression.